A THE ROLE OF THE WHISTLEBLOWERS IN THE FIGHT AGAINST CORRUPTION - Slamkov, Gjorgi; Filipovski, Zoran (International Scientific Journal Vision, 2019)
The paper deals with one of the instruments in the fight against corruption, ie "whistleblowers". It is an immediate source of information from the place where the crime was committed - illicit behavior, which has a long history but with different treatment. In fact, the complexity and pervasiveness of corruption require finding and applying a variety of means to tackle it, and whistleblowers can contribute at different times, both before committing harmful behavior, during execution and after completion. Especially the last decade, internationally, a lot of attention has been paid to whistleblowers. Among the numerous laws containing provisions on this anti-corruption instrument are the G20 High Level Principles for Effective Protection of Whistleblowers - The Osaka principles adopted in June 2019 and are a catalyst for improving the position of whistleblowers and their protection, in order to effectively combat corruption. In the same direction, at the EU level in 2019, the new EU Whistleblower Protection Directive has been adopted, which has several years of implementation in all member states. Its purpose is to increase the protection of whistleblowers and to raise awareness in the society of their meaning. Experience at EU level shows a non-uniform approach to the issue, i.e., some member states have no regulation, in other member states it is symbolically expressed, and in third member states (around ten) there is quality regulation of this anti-corruption instrument. The UK experience is particularly significant, and it is briefly contained in this paper. The situation is similar in the United States, namely, for nearly four decades there has been continuous work to improve federal and state regulation of whistleblowers. The paper presents the latest legal instruments for the protection of whistleblowers and guidelines for the future development of this instrument.